2020
DOI: 10.4185/rlcs-2020-1466
|View full text |Cite
|
Sign up to set email alerts
|

Educación en tiempos de pandemia: reflexiones de alumnos y profesores sobre la enseñanza virtual universitaria en España, Italia y Ecuador

Abstract: Introducción. Esta investigación realizó un estudio comparativo entre tres países muy impactados por el coronavirus a partir del análisis de las reflexiones de docentes y estudiantes sobre la enseñanza virtual universitaria durante la etapa de confinamiento. Metodología. El estudio, de carácter descriptivo, exploratorio y explicativo, aplicó encuestas, entre marzo y abril de 2020, a estudiantes y docentes de Periodismo, Comunicación y Educación de la Universidad Autónoma de Barcelona (España), Universidad de T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1
137

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(235 citation statements)
references
References 30 publications
(31 reference statements)
0
55
1
137
Order By: Relevance
“…Studies have shown that students establish a direct relationship between teaching quality and the materials utilized for developing the different teaching-learning processes [40][41][42][43][44][45].…”
Section: Materials Resourcesmentioning
confidence: 99%
“…Studies have shown that students establish a direct relationship between teaching quality and the materials utilized for developing the different teaching-learning processes [40][41][42][43][44][45].…”
Section: Materials Resourcesmentioning
confidence: 99%
“…In the current scenario, the use of Information and Communication Technologies represents an important step towards innovation [6] since ICTs bring us closer to new possibilities of knowledge distribution and acquisition of skills and new competences, and can also favor constructivist and collaborative learning [7]. The issue of digitization of higher education has opened a broad academic and professional debate [8][9][10] to detect where the forces of change and educational innovation goals should be directed [11,12] under the principle of improvement based on evidence and systematization of experiences which promote active citizenship and contribute to the development of the learner [13]. In this sense, the open innovation perspective highlight universities as capable agents driving innovation and fostering economic development providing knowledge flow [5].…”
Section: Introductionmentioning
confidence: 99%
“…This transformation of the education system is the response needed to meet two significant demands: The need to adapt to a global world and the evolution of a knowledge society [9]. Today, a third demand has been added, the need to adapt to a global pandemic context [10,11]. In fact, the emergence of new technologies has already introduced novel approaches to education: New training modalities (such as e-learning and blended learning) and mass education (such as mass and open online courses-MOOC); new ways for collaborative learning among students (WebQuest, project-based learning); improvement in the acquisition of skills with access to large amounts of information; changes in the roles of teachers and students; methodological changes (flipped classroom), etc., [12].…”
Section: Introductionmentioning
confidence: 99%